Hepatoprotective Activity Ofa Poly Herbal Extract In Carbon Tetra Chloride Intoxicated Hepatotoxicity In Male Albino Rats - KAVITHA.M; KARIMULLA.SK; DEEPAK KUMAR; VINOTH KUMAR.S; SATHISH KUMAR. R; GURUCHARAN.M (International Journal of Pharma and Bio Sciences, 2011)
The Poly herbal ethanolic extract (PHEE) was evaluated for its anti hepatotoxic potential against carbon tetrachloride (CCL4) induced hepatic damage in male albino rats. Ethanolic extract from the leaves of Melia azadirachta, seeds of Piper longum and whole plant of Eclipta alba at a dose level of 50 mg/kg body weight was administered orally daily once for 14 days. The substantially reduced levels of enzymatic anti-oxidants such as superoxide dismutase(SOD), catalase(CAT), glutathione peroxidase (GPx), glutathione-s-transferase(GST) and glutathione reductase (GR), due to carbon tetra chloride effect were restored to normal. Histopathological examination of liver sections of PHEE treated rats shows the restoration of normal tissues. Vitamin-E at a dose of 100 mg/kg taken as a standard reference also exhibited significant antioxidant activity against CCl4 induced Hepatotoxicity. The results of this study strongly justified that PHEE has a potent hepatoprotective activity against carbon tetrachloride